Pollen-pistil incompatibility in Petunia hybrida: changes in the pistil following compatible and incompatible intraspecific crosses. - Herrero, M; Dickinson, H (1979)
The structural events in the stigma and transmitting tissue of Petunia hybrida pistils that accompany compatible and incompatible intraspecific pollinations have been investigated in detail, together with the changes in reserve levels that also take place at this time. Many of these phenomena may be explained in terms of 3 phases of secretion by the cells in the upper regions of the transmitting tissue. The first, independent of pollination, results in the deposition of an intercellular matrix, rich in protein and carbohydrate. The second, triggered by pollination, although independent of the compatibility of the pollen grain, involves synthesis of molecules believed to be specific to the S(incompatibility)-gene system. The third phase of secretion occurs only following a compatible mating, and involves the transfer of stylar reserves to support the growth of the pollen tubes. These observations are discussed in terms of current models of the incompatibility mechanism operating in Petunia.